Digital Leadership and Sustainable School Improvement—A Conceptual Analysis and Implications for Future Research - Turgut Karakose; Tijen Tülübaş (Educational Process: International Journal)
Background/purpose – The study aimed to identify differences in the level of critical thinking dispositions of undergraduate students in Portugal according to their sociodemographic (gender, age) and academic (study field) characteristics.